An efficient algorithm for computing the coefficients of the characteristic polynomial of 2-D state-space models - Azimi-Sadjadi, Mahmood R., author; IEEE, publisher (Colorado State University. Libraries, 1987)
For 2-D systems described by a state-space structure, two different methods for computing the coefficients of their characteristic polynomial are introduced. The relative efficiencies of these methods are compared to that of Faddeeva's method. An efficient method is then chosen which can be used to compute the coefficients of the characteristic polynomial with a minimum number of multiplications.
Keywords: multidimensional (n-D) system; polynomials; transfer function matrices